Pottery Imports and their influence on local products in Aguntum, Noricum - Auer, Martin (Rei Cretariae Romanae Fautorum Acta, 2022)
During the 500 years of settlement history in the Roman Municipium of Aguntum pottery was imported for diverse purposes. Besides amphorae, especially table ware, cooking ware and mortaria have always been imported up to a certain amount. These products did definitely inspire regional products, especially when a certain imported vessel-form was no longer available. This applies for instance to Pompeian Red Ware during the 2nd century, but also to African Red Slip Ware during the 4th and early 5th centuries. Pottery for other purposes, like short time storage, shows strong regional traditions and its morphology and decoration is not influenced by imported wares. The focus of this paper lies on the comparison of assemblages from the Atrium House of Aguntum, which are dating to different periods from the 1st to the 5th century AD. The aim of this paper is to analyse in which ways imported cooking or table ware is interacting with local pottery during different time periods.